The Metaverse: Nature, Challenges, and Legal Approaches (Salam International Academic Journal, 2024)
Recent technological advancements have profoundly influenced human life, integrating a wide range of human activities into digital environments that require thoughtful adaptation and utilization. One of the most prominent manifestations of this transformation is the Metaverse—an emerging platform that reshapes how individuals interact in virtual spaces. This article examines the Metaverse as a new digital phenomenon, focusing on its nature, legal implications, and regulatory challenges. The primary objective of this research is to explore the fundamental essence of the Metaverse and address its legal dimensions, including the applicability of existing laws and the need for new legal provisions suited to this virtual realm. The study seeks to answer several key questions:   What is the Metaverse? What are the legal consequences of transactions conducted within it? What is an avatar, and what type of legal personality does it possess—independent or dependent? What laws govern this space, and how are they implemented? Additional implicit legal concerns are also reviewed in this context. The study adopts a comparative legal approach by examining how existing legal principles in the physical world relate to and can be applied within two-dimensional and three-dimensional virtual environments. Given the Metaverse's novelty and evolving nature, the research is grounded in current scholarly literature, acknowledging the provisional state of legal interpretation in this area. This paper begins by defining the Metaverse and then discusses its major legal and jurisprudential challenges. It concludes with practical and academic recommendations to support a deeper understanding of the Metaverse and to guide the development of appropriate legal frameworks for its governance.
Keywords: Avatar; Virtual Space; Metaverse; Digital Jurisprudence; Block chain